Additionality of the Clean Development Mechanism: Insights from Central American Case Studies - Lindsay, Abby (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: As part of the global response to climate change, the Clean Development Mechanism (CDM) was developed to involve developing countries in emission reductions by allowing them to sell developed countries carbon credits generated from emission-reducing projects. The CDM theoretically should help developing countries implement renewable energy, thus contributing to sustainable development, so this study focuses on the interaction between renewable energy, the CDM, and small developing countries. It analyzes the barriers to projects and the decision-making factors that determine whether or not projects are pursued in Honduras and Costa Rica. A host of barriers were found throughout the study, ranging from low electricity production revenues to investment barriers. The major decision-making factors were government policies, financial viability with and without revenue from the credits, and other barriers. Furthermore, since the carbon credits can be traded into cap and trade systems, the emission reductions must be additional. This study uses the barriers and decision-making factors to analyze the additionality of the CDM projects in comparison to the theory. The results found that while the additionality claims of the CDM projects were not false, in most cases the reasons cited would not likely have prevented the projects from being implemented. Implementation is more complex than the theory, and the next round of climate negotiations must take the difficulty ensuring strict environmental additionality into account.